Implementing Daily Management Systems to Support Sustained Quality Improvement in Ambulatory Surgery Centers. (1st April 2020) - Rakover, Jeffrey; Little, Kevin; Scoville, Richard; Holder, Barbara
Abstract: Quality improvement processes and management approaches that provide a foundation for continuous quality improvement can lead to improved patient care. The Institute for Healthcare Improvement developed a high‐performance management system (HPMS) for health care leaders and staff members to effect continuous quality control, and then conducted a pilot of the system in several ambulatory surgery centers (ASCs). The primary focus of the pilot program in the ASC setting was to understand the applicability of the theory of quality control using related practices (eg, standardized daily huddles, visual management boards) included in the modified HPMS. After implementing the new program, pilot site leaders observed an improvement of approximately 10 percentage points in their Agency for Healthcare Research and Quality patient safety culture survey scores. At the end of the pilot, the researchers concluded that ASC leaders can improve patient care and sustain improvement in their organizations using the HPMS practices.